Analisis Dimensi Smart City dan Urban Design di Taman Kambang Iwak Palembang - Husnul Masyitoh (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The development of smart cities has become a strategic priority for local governments seeking to enhance citizens’ quality of life, strengthen sustainable development, and improve public space management. Kambang Iwak Park in Palembang represents one of the city’s major urban green spaces that has undergone significant revitalization and serves as a case study for smart city implementation in public areas. This study analyzes the application of Cohen’s six smart city dimensions—Smart People, Smart Living, Smart Government, Smart Economy, Smart Mobility, and Smart Environment—and their relationship with Carmona’s six urban design dimensions. This qualitative–descriptive research utilizes visual observations, historical data, and facility documentation extracted from the provided presentation. The findings indicate that Kambang Iwak Park effectively integrates several smart city dimensions, particularly Smart Living, Smart Environment, and Smart Mobility. Nonetheless, issues such as irregular parking, insufficient smart services, and poorly organized street vendors remain challenges. The study concludes that integrating smart city principles with urban design concepts enhances public space quality and supports sustainable urban development in Palembang.